A Case of Multiple Antibiotic-Associated Hepatotoxicity in an Infant - S. S. Postnikov; N. V. Teplova; V. V. Nikolaev; F, K. Abdullaev; Yu. N. Solontsov; A. E. Ermilin; M. N. Kostyleva; Anna N. Gracianskaya (Безопасность и риск фармакотерапии, 2019)
Drug induced liver injury is one of the most frequent reasons for stopping treatment and the main cause of the onset and progression of acute liver failure, requiring liver transplantation. In children antibacterial drugs are on the first place in terms of hepatotoxicity, and the hepatocellular type is the most common type of liver damage. Often there is crosssensitivity within the same group of antibiotics, for example, beta-lactams. The aim: to analyze the causes of drug hepatotoxicity in the infant child while taking antibacterial agents. The article presents a clinical case of multiple hepatotoxicity caused by antibacterial agents such as beta-lactams, fluoroquinolones, sulfanilamides in one infant child, which suggests its genetic basis. It was shown that during therapy it is important to take into account the risk factors for hepatotoxicity (age, concomitant pathology, potential drug interactions with simultaneous use) and regularly evaluate the patient’s condition taking into account possible liver damage (including laboratory tests).